INTERAKTIFITAS BELAJAR UNTUK PENINGKATAN KETERLIBATAN AKTIF MAHASISWA: STUDI DI PRODI KPI UIN SUNAN KALIJAGA YOGYAKARTA - Yulia Rakhma Salsabila; M Agung Rokhimawan; Anisah Indriati (Raudhah - Proud To Be Professional, 2024)
This study aims to analyze the strategies used by lecturers to create an interactive learning environment in increasing students' active involvement in the Ulumul Qur'an course. This research is a qualitative research with a case study approach. Data collection was carried out with several techniques, namely observation, interviews and documentation. Data validity techniques using source triangulation and technical triangulation, data analysis techniques using the Miles and Huberman model include data reduction, data display and data withdrawal or verification. The results of this study show that this study shows that lecturers use strategies such as group presentations and discussions to encourage active student involvement. Group presentations gave students the opportunity to explore and deliver the material independently, which improved their understanding and communication skills. Meanwhile, Q&A discussions allow students to actively participate and exchange views in an interactive atmosphere. This makes the classroom atmosphere more lively, improves understanding of the material, and develops students' critical thinking skills, cooperation, and confidence. In addition, lecturers also use WhatsApp Group as a medium for questions and answers outside of class, so that students can continue to communicate and ask questions. Not only that, lecturers also provide assignments that can deepen students' understanding and creativity. This is the best